Assessment of Personal Hygiene for Adults with Diabetic Foot - Hussein H. Atia (Iraqi National Journal of Nursing Specialties, 2023)
Objective: The aim of the study is to assess the personal hygiene of adult patients withdiabetic foot.Methodology: ٨ descriptive study was carried out in Baghdad teaching hospital, Al-Karama teaching hospitaland Al-Kindey teaching hospital for the period of 10/1/2006 to 1/9/2006. A purposive "non probability" sampleof (100) patient.Questionnaire was constructed for achieving the purpose of the study. Data were collected through theapplication of the questionnaire and interview technique. Data were analyzed through descriptive statisticalapproach (frequency & percentage) and inferential statistical approach (chi-square ع correlation) by using ofSPSS.Results: The study results indicated that the range of age was between (56-60) year and most of them was male,married, read and write and the majority was smoking since (15) year ago and there is effect from personalhygiene on diabetic foot.Recommendation: The study recommended that educational programs should be constructed or designed forpersonal hygiene of patient newly diagnosed with diabetes, need for specialized nurses in the diabetic center andquit or reduce smoking.